Nanowires Recent Progress - Peng, Xihong (IntechOpen, 2021)
Low-dimensional structures have attracted extensive research interest due to their promising applications in nanotechnology. These low-dimensional materials have the potential to make revolutionary changes in science and technology because a reduction in size not only enables a faster speed and greater computing power but also helps reduce device form factors. As such, this book examines the behaviors of oxide nanowires, group III-V compounds, and other nanowires, including basic Si nanowires, metallic wires, and complex geometrical nanowires.